The Educational Philosophical Thoughts of Abu Hamid Al Ghazali (1058 - 1111) and ‎John Dewey (1859 - 1952): A Comparative Study‎ - Khasawneh, Omar ‎ (Jordan Journal of Educational Sciences, 2023)
The purpose of this study was to compare the educational thoughts of Al Ghazali and Dewey, two renowned scholars. In this study, the researcher surveyed Al Ghazali’s and Dewey’s efforts on education using methodological qualitative research methods, namely constant comparative analysis and discourse analysis, to discuss and evaluate their educational thoughts and to determine their educational philosophical thoughts in order to objectively validate their educational aspects as educators. Similarities and differences were discovered in the results of this study. The results indicated that the educational philosophical implementations of Islamic and Pragmatic thoughts in terms of school curricula, teaching methods, roles of teachers, roles of students, and school roles are viewed differently by each philosopher. Generally, Al Ghazali’s educational philosophical perspectives embody the idea that education involves the intellectual, mental, spiritual, ethical, moral, and physical elements of a person. Whereas, Dewey’s educational philosophical perspectives embody that the person, who is a social being, acquires knowledge through personal experiences and is born with intrinsic skills that education should develop. Education must aim at nurturing and promoting those skills to students’ fullest potential. Both scholars believed that promoting the well-being of children would be the school’s role by providing students with curricula enriched with a range of subject matters. Based on the study results, the researcher recommended that those who are concerned with the business of changing lives must realize the importance of teaching philosophy in order to establish their own. The researcher also made a number of recommendations, the most important of which was that future research on this topic should take into account only one educational aspect as opposed to combining all five aspects into a single study